El sector gastronómico y el desarrollo turístico en la ciudad de Riobamba, provincia de Chimborazo - Joselyn Yajaira, Lucero Flores (2024)
ABSTRACT: The present study analyzes the influence of the gastronomic sector and tourism development in the lovely city of Riobamba, located in the Chimborazo province, Ecuador. Gastronomy is an essential part of the cultural identity of this region, and its increasing recognition has generated a significant impact in the tourism field. In order for the proposed strategies to generate the desired results based on the gastronomic field and touristic development influence in Riobamba´s city, province of Chimborazo, objectives and hypotheses were propounded to help define the study, variables were described theoretically, which contributed necessary knowledge to be executed. In the methodological part, the hypothetical-deductive method was chosen, which allowed for proving or denying the proposed hypotheses, collecting, analyzing data, and presenting results; employing descriptive and field research. In the proposed and executed survey par, creativity, productivity, quality, and cultural conservation were related to the gastronomic sector and the touristic development in Riobamba´s city, Chimborazo. The obtained results showed the positive influence that Riobamba’s gastronomy has had on the increased touristic affluence and how it has contributed to improving the local economy. Furthermore, possible improvement areas and opportunities to further enhance touristic development were identified through gastronomy. With an integral evidence-based focus, this study tried to foment Riobamba´s positioning and growing as a touristic and gastronomic reference destination in Chimborazo´s province and further.